THE RELATIONSHIP BETWEEN DIGITAL READING ACTIVITY, READING ENGAGEMENT, AND READING COMPREHENSION AMONG EFL LEARNERS - Selfiah Anggraini Pratiwi; Indawan Syahri; Masagus Firdaus (Esteem Journal of English Education Study Programme, 2026)
The growth of digital technology has changed the way students read, learn, and interact with English texts. In many EFL classrooms, reading is no longer limited to printed books because students increasingly access materials through smartphones, laptops, and online platforms. This shift gives learners wider exposure to authentic texts, yet it also introduces new demands related to navigation, attention control, and strategic reading. In such contexts, reading comprehension is shaped not only by students’ access to digital texts but also by how actively they engage with what they read. This study examined the relationship between digital reading activity, reading engagement, and reading comprehension among eleventh-grade EFL learners. A quantitative correlational design was used. Data were collected through a digital reading activity questionnaire, a reading engagement questionnaire, and a reading comprehension test, then analyzed using descriptive statistics, Pearson product-moment correlation, and multiple regression. The findings show that digital reading activity was positively and significantly related to reading comprehension. Reading engagement also had a positive and significant relationship with comprehension. In addition, both variables simultaneously contributed to students’ reading comprehension performance. These findings suggest that digital reading becomes more academically meaningful when it is accompanied by active emotional, behavioral, and cognitive engagement during reading.